PENGAJARAN DAN PERJUANGAN: PERAN TOKOH-TOKOH PRIBUMI LULUSAN KWEEKSCHOOL SEBAGAI PEMBANGKIT NASIONALISME INDONESIA ABAD 19 - Sidqi Alfarez (Siginjai: Jurnal Sejarah, 2022)
Modern education in Indonesia is characterized by the emergence of western education brought by the Dutch since the VOC of the 1600s until the emergence of ethical politics in the 19th century in the Dutch East Indies. One form of development of western modern education is the special education of indigenous teachers, namely kweekschool. The Kweekschool institution will be the forerunner to the increasing quality of education in the Dutch East Indies after the implementation of ethical politics.   Methodology in waiting refers to historical qualitative which includes topic selection, heuristics, verification, interpretation, and historical writing.   Therefore, the problems taken from the subject matter generally surround Kweekschool whose impact on the lives of the indigenous people of the Dutch East Indies.  Until Kweekschool graduates and their work in the movement.